The Convergence of Drug Trafficking and Terrorism: Uncovering the Dynamics of Narco-Terrorism - Kiki Kristanto; Zico Junius Fernando; Ridwan Arifin; Anis Widyawati (Yustisia, 2024)
Drug trafficking and terrorism have seriously threatened many countries' global stability and national security. However, in recent years, there has been an increasing trend of convergence between drug trafficking and terrorism, forming a phenomenon known as narco-terrorism. The article seeks to reveal the relationship between narcotics trafficking and terrorism, a phenomenon often called narco-terrorism. This study's normative legal research method utilizes conceptual and comparative approaches. The results reveal that the convergence between drug trafficking and terrorism seriously impacts security, economy, and social stability. The drug trade provides a substantial source of income for terrorist groups, enabling them to expand their networks, purchase weapons, and launch terror attacks. Conversely, terrorist groups provide drug traffickers protection, infrastructure, and access to drug markets. This study provides important insights for governments, law enforcement agencies, and international organizations in designing effective strategies and policies to counter narco-terrorism. By understanding the dynamics and mechanisms of convergence between drug trafficking and terrorism, appropriate preventive and countermeasures can be taken to mitigate the threats faced by the global community.